Spatio-temporal variations in hexachlorobenzene partitioning in a near shore Antarctic marine environment from a one-dimensional coupled ecosystem-chemical distribution model - L Bates, Michael; W Hawker, Darryl; Cropp, Roger (Journal of marine systems, 2019)
Hexachlorobenzene (HCB) is an example of a persistent organic pollutant (POP) that is relatively abundant and widespread in near shore Antarctic marine environments. By definition, POPs may distribute with an ecosystem, bioaccumulating and potentially reaching hazardous levels in some organisms. Modelling approaches may provide insight into this behaviour and complement physical sampling that is difficult in such environments. Here, a dynamic, trophically complex ecosystem (biological) model comprising biological groups from plankton to apex predators is coupled to a mass conserving, fugacity based chemical distribution model with vertical resolution of the seawater compartment. The model accommodates seasonal variations in solar irradiance, sea ice coverage, and boundary layer air temperature. The greatest proportion of the HCB is predicted to be in sediment with comparatively little intra-annual variation. For biota, highest lipid based concentrations are in aerial seabirds, baleen whales and seals but considerable seasonal variation is apparent. The POPcline, the water depth where vertical HCB concentration gradient is greatest, is coupled with the base of the mixed layer throughout the Antarctic year. Seasonal partitioning of POPs in Antarctic environments is shown to be subject to oscillating or “flip-flop” dynamics with significantly different controlling factors in summer and winter. In summer, HCB in the surface waters, where most of the biological activity is occurring, is isolated from the sediments that contain most of the POP mass. During winter however, fractional sea ice cover increases turbulent diffusion and the mixed layer and POPcline deepen increasing homogenisation in water column. Surface waters are more likely to come into direct contact with sediments, and biota such as krill migrate to the ocean floor and feed on detritus produced from summer plankton blooms that has since sunk to the ocean floor. •A vertically-resolved model of POP (HCB) dynamics in an Antarctic ecosystem•Simulations predict a POP-cline associated with sea surface mixed layer.•Spatio-temporal variations in POP concentrations and processes are evident.•POP dynamics in summer are effectively an ocean-atmosphere system.•POP dynamics in winter are effectively an ocean-sediment system.